Surveying the vascular flora of the Iberian Central Range: a critical checklist of the Ávila province flora - Luceño, Modesto; Rogelio Sánchez-Villegas; Quirós de la Peña, Begoña; Manuel Sánchez-Villegas; Robles Fernández, José Luis; Francisco J. de Sande Velicia; Víctor Javier Marugán; Alberto Arribas Martín; José Antonio López Sáez; Bariego, Patricio; Rico, Enrique; Enrique Maguilla (Mediterranean Botany, 2025)
Despite its proximity to cities with important botanical institutions such as Madrid and Salamanca, and its location between important mountain ranges (Gredos and Malagón mountain ranges), the flora of the province of Ávila had not been studied comprehensively until now. In this article, we present the first checklist of the vascular flora of this province, which is the result of a thorough critical bibliographic review, numerous field trips, and the study of materials preserved in Iberian herbaria, mainly those that house the majority of the collections made in the province. The taxonomic and nomenclatural treatment takes into account the results of the latest monographic works and, particularly, the molecular phylogeny studies conducted over three decades. These studies have substantially changed the classification to align it with the evolutionary processes that have contributed to the current plant biodiversity. We have accepted a total of 1960 taxa (species and subspecies), with 1797 considered native and 163 introduced. Additionally, we present the floristic spectrum of the province and the state of conservation of its flora. All of this is discussed in light of the data provided by the complete checklists available from neighbouring provinces. For each taxon, we highlight its presence or absence in the three ecological regions into which we have divided the province (La Moraña region, Sierra de Gredos, and Sierra de Malagón). Where necessary, we provide observations regarding its distribution, taxonomy, or nomenclature. Notably, we include the genus Exaculum in Schenkia, leading us to propose a new nomenclatural combination.